Pengelolaan Program Merdeka Belajar Kampus Merdeka dalam Pembelajaran Daring Jurusan Ilmu Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sriwijaya - Nur Budiyanto, Muhammad; Salsabila, Adinda; Ermanovida (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2022)
This research was aimed to analyzed and described the management of the MBKM program Department of Public Administration, Faculty of Social and Political Sciences, Sriwijaya University. The background of this research is because the MBKM program policy is a new policy and still causes many problems, one of which is in the data collection process for students who take part in the MBKM program, there are still students who have not been registered by the majors that are followed. Public Faculty of Social and Political Sciences Sriwijaya University using the theory of management functions by George R Terry which consists of four dimensions between planning. Organizing, Implementing, and Monitoring. The research method used is a qualitative research method. Considering the results of the analysis of each data in the MBKM program, Department of Public Administration, Faculty of Social and Political Sciences, Sriwijaya University, it has been running well based on the four dimensions proposed by George R Terry, although in practice there is still no special assignment made for the management team and is still there are problems in the process of converting grades and sometimes students do not confirm to the department or academic supervisor. The suggestion that the author can give is that in the function of implementing the MBKM program, the researcher suggests to the Department of Public Administration to place more emphasis on students following the SOP when they want to join the MBKM program in order to minimize obstacles such as converting values ​​and data that are not recorded by the department